The Pengaruh Stres Kerja terhadap Kinerja Karyawan PT. Bank Rakyat Indonesia Kantor Cabang A. Rivai Palembang - M Rafli Afda; Isni Andriana; Lina Dameria Siregar (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study aims to determine the effect of work stress on employee performance at PT. Bank Rakyat Indonesia Branch Office A. Rivai Palembang. The population in this study were all employees at PT. Bank Rakyat Indonesia Branch Office A. Rivai Palembang using a sample of 60 respondents. The data collection method used in the study was obtained from a questionnaire. The analysis technique used is simple linear regression analysis. Data processing in this study using the SPSS software program (version 24.00). Based on the results of the analysis, it was concluded that work stress had a negative and significant effect on employee performance at PT. Bank Rakyat Indonesia Branch Office A. Rivai Palembang. Keywords: Job Stress; Performance; Employees.